Dysphagia and thoracoabdominal aneurysm - Taylor, C (BMJ Group, 2001)
Two elderly patients who presented with gradually progressive dysphagia are described. Investigations excluded an intraluminal obstruction and showed extrinsic compression of the oesophagus by an aneurysmal aorta. Surgery was not performed and they were successfully managed with a liquid diet.   Keywords: dysphagia; aortic aneurysm; vascular compression